Effects of diet complexity and processing method on growth performance and nutrient digestibility in nursery pigs - Traylor, S.L.; Hines, Robert H.; Johnston, S.L.; Sorrell, P.; Behnke, Keith C.; Hancock, Joe D.; DeRouchey, Joel M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A complex diet formulation resulted in greater digestibility of nutrients and a trend for greater ADG for d 0 to 14 of the experiment. However, for d 14 to 28 and overall (d o to 28), diet complexity did not affect growth performance. In contrast, pelleting improved essentially every response criterion especially in simple diets. Expander conditioning before pelleting increased overall digestibility of nutrients and of F/G compared to standard conditioning, but again, the response was most pronounced with the simple diet formulations.
Keywords: Swine; Expander; Pellets; Nursery pigs